1996
DOI: 10.1007/bf01849631
|View full text |Cite
|
Sign up to set email alerts
|

Risk for ovulation in women taking a low-dose oral contraceptive (Microgynon) when receiving antibacterial treatment with a fluoroquinolone (ofloxacin)

Abstract: The possibility of escape ovulation in women using a fluoroquinolone ofloxacin for antibacterial treatment at a dose of 200 mg twice daily for 7 days when taking a combined oral contraceptive (Microgynon, 150 micrograms levonorgestrel and 30 micrograms ethinyl estradiol) was studied in 20 women. By using a placebo-controlled, randomized, cross-over design 6 contraceptive pill cycles were followed. Follicle-stimulating hormone and estradiol concentrations were measured on tablet days 5-8, 19-21; progesterone wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…25 Two additional trials reported no ovulation by serum progesterone and/or monitoring of follicles on ultrasound scanning in OC cycles with and without temafloxacin or ofloxacin. 26,27 Pharmacokinetic outcomes. Two studies reported no change to HC pharmacokinetic with fluoroquinolones.…”
Section: Tetracyclines and Ocs (Table 2; Appendix D)mentioning
confidence: 99%
“…25 Two additional trials reported no ovulation by serum progesterone and/or monitoring of follicles on ultrasound scanning in OC cycles with and without temafloxacin or ofloxacin. 26,27 Pharmacokinetic outcomes. Two studies reported no change to HC pharmacokinetic with fluoroquinolones.…”
Section: Tetracyclines and Ocs (Table 2; Appendix D)mentioning
confidence: 99%
“…A small, randomised, doubleblind, crossover study investigated the effect of ofloxacin 200 mg twice daily on ovulation in women using a 30 µg EE COC. 99 No evidence of ovulation, by ultrasound scan and serum progesterone, was found.…”
Section: Other Drugsmentioning
confidence: 90%
“…22 Two small, prospective, randomised-controlled trials investigated the effects of antibiotics (ciprofloxacin and ofloxacin) on markers of ovulation in women using COCs and found no evidence of ovulation. 24,25 Despite lack of evidence of the effects of antibiotics on gut flora, additional contraception is advised when starting a new broad-spectrum, nonenzyme-inducing antibiotic and for 7 days after discontinuation in keeping with previous Faculty Guidance. 26 Women who are established on a nonenzyme-inducing antibiotic long-term do not require additional contraception unless they change to a different antibiotic.…”
Section: Methotrexatementioning
confidence: 99%